Izboljšanje dostopa do trga za mala in srednje velika podjetja ter mikropodjetja v mestih Južnoafriške republike - Rogerson, Christian M. (Urbani izziv, 2013)
Since the democratic transition of 1994, the promotion of the small, medium and micro-enterprise (SMME) economy has been a core focus of South African government policy. With high levels of unemployment and poverty in urban areas, the impact of this policy intervention is most critical for city development. Given South Africa's chequered history, the national government'sfocus is on transforming the prospects for enterprises owned by black South Africans, who were disadvantaged under apartheid. This article examines the range of contemporary policy initiatives to address business constraints on market access and catalyse new market opportunities for black-owned enterprises in urban South Africa. The article concentrates on two themes: 1) building links into private sector supply chains, especially through supplier diversity, and 2) building links into public sector markets through public procurement. It is shown that current policy directions recognise that the national government has a limited capacity to implement SMME improvement and build competitive black-owned SMMEs by itself, which has prompted support for private sector initiatives. In addition, the government is struggling to practice what it preaches and use its own procurement capacity to assist black-owned SMMEs.
Keywords: črnci; dostopnost; Južnoafriška republika; lastništvo; mala podjetja; podjetništvo; srednja podjetja; trg; vladna politika